PENGARUH PENGUNGKAPAN INFORMASI CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS DAN PEMBAGIAN DIVIDEN PADA HARGA SAHAM - Arimbawa, Putu; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
This study is aimed at know ing the effect of CSR profitability information disclosure and describing the dividend payment to the stock price of manufacturing company group LQ45 in BEI period 2010-2013. Data used in this study belong to the secondary data in the form of time series year 2010 until 201 3 with t he containing financial information of manufacturing company group LQ45 in BEI were downloaded from the website www.idx.co.id. T echnique analyzed using the multiple linier regression with SPSS program. The research result s show that partially, CSR an d profitability do no t have the significant effect , whereas dividend payment has the significant effect to stock price of the manufacturing company group LQ45 in BEI period 2010-201.
Keywords: stock price, CSR, profitability and dividend payment